2004
DOI: 10.1016/j.biocel.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Purification, identification and characterisation of seprase from bovine serum

Abstract: ABBREVIATIONSAMC, 7-amino-4-methylcoumarin; BCA, bicinchoninic acid; CPC, calcium phosphate cellulose; DFP, diisopropylfluorophosphate; FPLC, fast protein liquid chromatography; HIC, hydrophobic interaction chromatography; PO, prolyl oligopeptidase; TFA, trifluoroacetic acid; Z, N-benzyloxycarbonyl; ZIP, Z-Pro-prolinal-insensitive Z-Gly-Pro-AMC-hydrolysing peptidase. ABSTRACTThe study and identification for the first time of a soluble form of a Seprase activity from bovine serum is presented. To date, this act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 26 publications
2
42
1
Order By: Relevance
“…Interestingly, Collins et al 25 have found FAP-like activity in bovine serum, which is in accord with our report of APCE in human plasma. APCE may be a soluble, circulating derivative of FAP, resulting from cleavage of the Cys23-Ile24 bond in the transmembrane or extracellular domain of FAP, and if so, its presence in plasma could have an impact on the use of therapeutic agents designed to target FAP at the tissue level.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, Collins et al 25 have found FAP-like activity in bovine serum, which is in accord with our report of APCE in human plasma. APCE may be a soluble, circulating derivative of FAP, resulting from cleavage of the Cys23-Ile24 bond in the transmembrane or extracellular domain of FAP, and if so, its presence in plasma could have an impact on the use of therapeutic agents designed to target FAP at the tissue level.…”
Section: Introductionsupporting
confidence: 93%
“…These values are about 2-fold smaller when compared to a K m of 0.270 mM for bovine FAP toward Z-Gly-Pro-AMC. 25 Using Z-Gly-Pro-AMC, we determined k cat values for human rFAP and APCE to be 30.5 minute Ϫ1 and 32.2 minute Ϫ1 ; k cat for bovine FAP has not been reported. For Ala-Pro-AFC substrate, human rFAP and APCE have K m and k cat values of 0.323 mM and 64.7 minute Ϫ1 and 0.272 mM and 59.7 minute Ϫ1 , respectively, in contrast to 0.20 mM and 120 minutes Ϫ1 , which Sun et al 32 reported for full-length human rFAP.…”
Section: Sequence Analysis Of Rfap and Apcementioning
confidence: 97%
“…The active enzyme is a homodimer of two 97-kd subunits, and a soluble form of FAP␣ has also been reported (131,132). In contrast to DPP-4, FAP␣ typically is not expressed in normal tissues.…”
Section: )mentioning
confidence: 99%
“…Reports show that the gelatinase activity of Seprase was completely blocked by serine-protease inhibitors, including DFP and PMSF [11,25] [40]. Table 1 summarises some of the biochemical properties of Seprase.…”
Section: Biochemical Properties Of Seprasementioning
confidence: 99%